If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 + 4x = -2x + 31 Reorder the terms: -35 + 4x = 31 + -2x Solving -35 + 4x = 31 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -35 + 4x + 2x = 31 + -2x + 2x Combine like terms: 4x + 2x = 6x -35 + 6x = 31 + -2x + 2x Combine like terms: -2x + 2x = 0 -35 + 6x = 31 + 0 -35 + 6x = 31 Add '35' to each side of the equation. -35 + 35 + 6x = 31 + 35 Combine like terms: -35 + 35 = 0 0 + 6x = 31 + 35 6x = 31 + 35 Combine like terms: 31 + 35 = 66 6x = 66 Divide each side by '6'. x = 11 Simplifying x = 11
| Y+6=3(x-2) | | 8.7n+4.5-3.2n=375 | | 3y+7=x-13 | | P=$1440/4 | | 3(2y+1)-5(12y-7)+(6y-1)=37 | | P=$1440/5 | | 13.2=t4.4 | | -4r-9=-14-3r | | x+4+3x=31 | | -2x-17=13-4x | | 4s^2=-36 | | -2Xx=5 | | 12-9x+45=-1+x | | R+25=9 | | 3x+1+4x=7x-3 | | 5d=9/10 | | 6x-17=13-4x | | 27.50x+23.25x=17 | | -9b=153 | | 28=4+11 | | (8x+1)(x-7)=(2x-3)(4x+5) | | 5(z+1)=4(z-8)+z | | 2q+58=-2+-4q | | y=-2cos(x) | | -2q+58=2+-4q | | (3/4×).(y/3) | | R/8=9 | | 1/2(4x=6)=0 | | -4x+.5y=1 | | 4a-4=8+2 | | x-32=-4x+23 | | x^3-9x^2+72x-260=0 |